2002
DOI: 10.1080/02699930143000554
|View full text |Cite
|
Sign up to set email alerts
|

Negative processing biases predict subsequent depressive symptoms

Abstract: This study investigated the possible relationship between negative processing biases and subsequent depression. The Scrambled Sentences Test (SST), a measure of processing bias, was administered to a large sample of undergraduates. Participants also completed self-report measures of thought suppression tendencies, current level of depression, and lifetime worst-depression symptoms. High scores on the SST, reflecting a negative processing bias, predicted depression symptoms measured 4 to 6 weeks later, even aft… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
199
1
5

Year Published

2003
2003
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 224 publications
(211 citation statements)
references
References 44 publications
6
199
1
5
Order By: Relevance
“…Results from longitudinal studies with adults suggest that information processing paradigms may reveal key processing biases underlying depression. Cognitive biases predict change in depressive symptoms in community samples (Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002). Pregnant mothers recalling more negative words on a self-referential encoding task demonstrate more symptoms of depression following childbirth (Bellow & Hill, 1991).…”
Section: Reviewmentioning
confidence: 99%
“…Results from longitudinal studies with adults suggest that information processing paradigms may reveal key processing biases underlying depression. Cognitive biases predict change in depressive symptoms in community samples (Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002). Pregnant mothers recalling more negative words on a self-referential encoding task demonstrate more symptoms of depression following childbirth (Bellow & Hill, 1991).…”
Section: Reviewmentioning
confidence: 99%
“…Prior studies with this task revealed differences in interpretative tendencies between depressed and non-depressed samples (e.g., Hedlund & Rude, 1995;Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002). In this study, each trial started with a fixation point at the left side of the screen (to elicit left-toright reading) followed by a stimulus display depicting either a neutral or an emotional scrambled sentence.…”
Section: Interpretation Bias a Computerized Version Of The Scrambledmentioning
confidence: 99%
“…Importantly, longitudinal studies and cognitive bias modification (CBM) research (i.e., experimental manipulation of processing biases) have shown that cognitive control deficits (Siegle, Ghinassi, & Thase, 2007;Zetsche & Joormann, 2011), biases in attention (Beevers & Carver, 2003;, interpretation (Blackwell & Holmes, 2010;Holmes, Lang, & Shah, 2009;Rude, Valdez, Odom, & Ebrahimi, 2003;Rude, Wenzlaff, Gibbs, Vane, & Whitney, 2002), and memory processes (Johnson, Joormann, & Gotlib, 2007;Raes, Williams, & Hermans, 2009;Sumner, Griffith, & Mineka, 2010) can predict and contribute to the onset and maintenance of depressive symptoms. Moreover, these distorted cognitive processes can be found in at-risk (Dearing & Gotlib, 2009;Joormann, Talbot, & Gotlib, 2007;Kujawa et al, 2011;Taylor & Ingram, 1999) and remitted (Fritzsche et al, 2010;Gilboa & Gotlib, 1997;Hedlund & Rude, 1995;, 2010 depressed samples.…”
Section: Cognitive Biases and Vulnerability For Depressionmentioning
confidence: 99%
“…Although empirical data from longitudinal studies have found that biases in attention (Beevers & Carver, 2003), interpretation (Rude, Durham-Fowler, Baum, Rooney, & Maestas, 2010;Rude et al, 2003;Rude et al, 2002), memory (Johnson et al, 2007;Sumner et al, 2010) and impairments in cognitive control (Zetsche & Joormann, 2011) can predict depressive symptoms and clinical depression, it is COMBINED COGNITIVE BIAS HYPOTHESIS IN DEPRESSION 25 notable that the obtained effects sizes are often small to moderate. In line with Mathews and MacLeod (2005) we believe that biased cognitive processes can have substantial effects on depression through their mutual interactions and interaction with stressful live events, affecting emotional reactivity to stress that may subsequently lead to depressive symptoms and episodes.…”
Section: Predicting Depressionmentioning
confidence: 99%